1986
DOI: 10.1172/jci112496
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human c-fms proto-oncogene product (colony-stimulating factor-1 receptor) on peripheral blood mononuclear cells and choriocarcinoma cell lines.

Abstract: The c-fins gene product is related, and possibly identical, to the receptor for the mononuclear phagocyte colony stimulating factor, CSF-1. Using antisera to a recombinant v-fins-coded polypeptide, glycoproteins encoded by the human c-fms locus were detected in mononuclear cells from normal peripheral blood and in promyelocytic HL-60 cells 24 h after induction of monocytic differentiation with phorbol ester. The 150-kD human c-fins-coded glycoprotein was expressed at the cell surface, was active as a tyrosine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…The Table 1 (3,8,9,20), has many structural similarities to the epidermal growth factor (EGF) receptor (29 (49,50). The v-fms gene product resembles v-erbB in that both have undergone COOHterminal modifications compared to the protein encoded by their cellular homologues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Table 1 (3,8,9,20), has many structural similarities to the epidermal growth factor (EGF) receptor (29 (49,50). The v-fms gene product resembles v-erbB in that both have undergone COOHterminal modifications compared to the protein encoded by their cellular homologues.…”
Section: Discussionmentioning
confidence: 99%
“…M-CSF acts on progenitor and mature cells of the monocyte-macrophage lineage to induce cell proliferation, maintain cell viability, and induce biochemical differentiation (4)(5)(6)(7). The c-fms gene product is also expressed in placenta and choriocarcinoma cells and indeed may have a wider role in cell growth and differentiation beyond the monocyte-macrophage lineage (8,9). The v-fms oncogene is part of the genome of the Susan McDonough strain of feline sarcoma virus (SM-FeSV), a virus that causes fibrosarcomas in cats (10)(11)(12).…”
mentioning
confidence: 99%
“…Evidence from transgenic models suggests that c-fms encodes for the sole receptor for CSF-1 (Dai et al, 2002). We and others have found that c-fms and/or CSF-1 are expressed by the tumor epithelium in several human epithelial cancers (Kacinski et al, 1988(Kacinski et al, , 1991Rettenmier et al, 1989;Filderman et al, 1992;Ide et al, 2002); elevated levels of c-fms and CSF-1 are associated with poor prognosis (Kacinski et al, 1988;Tang et al, 1990;Price et al, 1993;Chambers et al, 1997Chambers et al, , 2009Scholl et al, 1993;Kluger et al, 2004;Sapi 2004). In human breast cancer, 94% of in situ and invasive lesions express c-fms (Kacinski et al, 1991;Flick et al, 1997), while 36% express both CSF-1 and c-fms (Kacinski et al, 1991;Scholl et al, 1993).…”
Section: C-fms and Breast Cancermentioning
confidence: 92%
“…This has revealed a somewhat unexpected role of at least two haemopoietic growth factors, GM-CSF and M-CSF (Rettenmier et al, 1986) in foetal trophoblast growth and action. Baldwin et al, 1989), human endothelial cells (Bussolino et al, 1989) human osteoblast-like cells (Evans et al, 1989) and human placental cells (Wegman et al, 1989).…”
Section: Introductionmentioning
confidence: 99%